A Preliminary Intellectual Scope of Research on Celebrity Endorsement from Bibliometric Study - Fei, Lu Yi (International Journal of Multidisciplinary in Management and Tourism, 2023)
This study uses bibliometric analysis software to provide conceptual insight into research on celebrity endorsement. The bibliometric data was retrieved from Sciencedirect.com. The results show five clusters of themes that relate to research on celebrity endorsement, and the most attention is being paid to consumer behaviors, which shows relevant constructs such as trustworthiness, credibility, attractiveness, brand attitude, congruence, and purchase intention. This study also presents the theoretical implications, which illustrate theories such as the theory of parasocial interaction, stimulus-organism-response, and as a suggestion for further research, the theory of planned behavior. The limitations are also discussed, and suggestions are provided.